Characterization Antimicrobes of Pliek U, A Traditional Spice of Aceh - NURLIANA NURLIANA; LISDAR IDWAN SUDIRMAN (Bogor Agricultural University, Indonesia, 2009)
Pliek u obtained by traditionally fermentation of coconut meat is a potential source of antimicrobial compounds. This research was aimed to detect of their active compounds by bioautographic method and to analyze their chemical composition by GC-MS. For this purposes, pliek u was extracted with ethanol 96% to get crude ethanol extract of pliek u (EEP) and to get ethanol extract of residual pliek u (EERP) which was previously extracted by hexane. Crude EEP was separated into four bioautographic spots with different Rfs (0.93, 0.71, 0.19, and 0.10) which were all shown to be active against Staphyloccoccus aureus. Similar result was shown by EERP, but only resulted three bioautographic spots (Rfs 0.77, 0.63, and 0.4). Crude EEP consisted of 22 components representing 99.98% with fatty acids, ester, alcohol as major constituents and aliphatic hydrocarbon. EERP consisted of 9 components representing 99.80% with alcohol as major constituents and fatty acids, ester, 4-Dibenzofuramine and amine as minor constituents. The present of many active compounds in pliek u supports the use of pliek u as spice to improve the quality of food and encourages further studies to determine those active compounds. Key words: antimicrobe detection, chemical composition, pliek u